Detection issues with many BS antennas available for bandwidth efﬁcient uplink transmission in a MU-MIMO system - Torres, Paulo (2016)
This paper is concerned with Single Carrier (SC)/Frequency Domain Equalization (FDE) for bandwidth efﬁcient uplink block transmission, with Quadrature Amplitude Modulation (QAM) schemes, in a Multi-User (MU) Multi-Input Multi-Output (MIMO) system. The number of Base Station (BS) receiver antennas is assumed to be large,but not necessarily much larger than the overall number of transmitter antennas jointly using the same time/frequency resource at Mobile Terminals (MT). In this context, we consider several detection techniques and evaluate, in detail, the corresponding detection performances (discussed with the help of selected performance bounds), for a range of values regarding the number of available BS receiver antennas. From our performance results, we conclude that simple linear detection techniques,designed to avoid the need of complex matrix inversions, can lead to unacceptably high error ﬂoor levels; however, by combining the use of such simple linear detectors with an appropriate interference cancellation procedure - within an iterative Decision-Feedback (DF) technique, a close approximation to the Single-Input Multi-Output (SIMO) Matched-Filter Bound (MFB) performance can be achieved, even for 64-QAM schemes, after a few iterations.